2012
DOI: 10.1016/j.mechmat.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Induced anisotropy by the Mullins effect in filled silicone rubber

Abstract: This study is concerned with the experimental characterization of anisotropy induced by the Mullins effect in a particle-reinforced silicone rubber. Experimental data concerning the influence of type and direction of initial loading on the subsequent stress softening are quite scarce. In this scope, a set of experimental tests were carried out on a filled silicone rubber. Uniaxial tensile tests and bulge tests were used to precondition the samples, i.e., to induce some primary stress softening. In both cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 24 publications
5
78
0
Order By: Relevance
“…Its mechanical properties were previously investigated [7,20,21] and it was shown that this material exhibits stress-softening, occurring mainly during the first load, hysteresis and temperature dependent behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Its mechanical properties were previously investigated [7,20,21] and it was shown that this material exhibits stress-softening, occurring mainly during the first load, hysteresis and temperature dependent behavior.…”
Section: Methodsmentioning
confidence: 99%
“…This material was already used in previous works and some non linear phenomena as hysteresis, relaxation [11,21] and induced anisotropy [13] were already studied. As illustrated by [21], the Mullins effect is the prevailing phenomenon so the experimental results focus on the study of this phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…The filled silicone rubber used in this study presents an induced anisotropy [11,13]. [19] developed a constitutive equation written with strain invariants to predict the behavior of this material.…”
Section: Constitutive Equation Of the Bulk Materials Filled Silicone Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain induced crystallization in filled natural rubber is known to retard crack growth, increasing significantly the critical energy release rate compared to non-crystallizing filled gum like SBR (Buist 1945 Diani et al 2009), exhibited by carbon-black filled rubbers, affects the resistance to crack propagation. The Mullins effect experienced by filled rubbers when first stretched above the maximum stretch ever applied, induces anisotropic softening (Diani et al 2006, Itskov et al 2006, Machado et al 2012 for instance) which consequences on the resistance to crack propagation remains unknown. Since the anisotropic softening may be characterized by a three-dimensional envelope that has been assessed on experimental evidences (Merckel et al 2012), it is relevant to study not only the impact of the softening magnitude but also its directional aspect on crack propagation.…”
Section: Introductionmentioning
confidence: 99%